Проблеми будівництва багатоповерхових будівель в умовах щільної міської забудови - Степанюк, Р. Б. (Ways to Improve Construction Efficiency, 2014)
The article provides examples of international practical experience of countries where we have successfully accomplished the construction of multi-storey monolith - frame buildings in dense urban areas, such as the United States of America, United Arab Emirates, Russia and objects implemented and those which are under construction nowadays in Ukraine. With the rapid development of multi-storey frame - monolithic construction in the world, and now in Ukraine, a separate item becomes a question of the technical implementation of the project. During the construction of multi-storey monolith - frame buildings in the conditions of dense city construction, it is necessary to consider that they have their own specifics, which significantly distinguishes them from the ordinary buildings. The article contains the main construction and technological peculiarities of construction of multi-storey monolith - frame buildings in dense urban areas. With the development of a multi-storey frame - monolithic construction designed with several structural systems, which are given in the article.